2015
DOI: 10.4103/0366-6999.168963
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Nutrition Support Team Improves Clinical and Hospitalized Outcomes of Esophageal Cancer Patients with Concurrent Chemoradiotherapy

Abstract: Background:The prevalence of malnutrition is very high in patients with cancer. The purpose of this study was to investigate whether or not a nutrition support team (NST) could benefit esophageal cancer patients undergoing chemoradiotherapy (CRT).Methods:Between June 2012 and April 2014, 50 esophageal cancer patients undergoing concurrent CRT were randomly assigned into two groups: The NST group and the control group. The nutritional statuses of 25 patients in the NST group were managed by the NST. The other 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 15 publications
(14 reference statements)
1
44
0
1
Order By: Relevance
“…However, the nutritional support group had a significantly lower incidence of severe and total neutropenia compared with the routine care group (p = .042 and.007 respectively). Cong and his co-workers also reported a significant difference in the percentage of patients who experienced grade ≥2 bone marrow suppression (20% and 48% in the nutritional support group and the control group, p = .037; Cong et al, 2015). Immune analysis in our study also showed that nutritional support was effective in helping the immune system during CCRT (as shown in Table 6).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the nutritional support group had a significantly lower incidence of severe and total neutropenia compared with the routine care group (p = .042 and.007 respectively). Cong and his co-workers also reported a significant difference in the percentage of patients who experienced grade ≥2 bone marrow suppression (20% and 48% in the nutritional support group and the control group, p = .037; Cong et al, 2015). Immune analysis in our study also showed that nutritional support was effective in helping the immune system during CCRT (as shown in Table 6).…”
Section: Discussionsupporting
confidence: 71%
“…Cong and his co-workers also reported a significant difference in the percentage of patients who experienced grade ≥2 bone marrow suppression (20% and 48% in the nutritional support group and the control group, p = .037; Cong et al, 2015). However, the nutritional support group had a significantly lower incidence of severe and total neutropenia compared with the routine care group (p = .042 and.007 respectively).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nutritional intervention was also associated with a lower average length of hospital stay and in-patient cost [111]. Furthermore, nutritional intervention improved survival of esophageal cancer patients treated with definitive chemoradiotherapy.…”
Section: Nutritional Interventions During Chemoradiotherapymentioning
confidence: 94%
“…Dukungan nutrisi meliputi terapi obat, perawatan, diet dan peran interdisipliner diantaranya dokter, apoteker, ahli gizi dan perawat (Cong et al, 2015;Maree, 2011). Dukungan nutrisi merupakan tugas penting dalam perawatan pasien kritis.…”
Section: Pendahuluanunclassified